Kemampuan Menghafal Al-Qur’an dan Capaian Hasil Belajar Santri: Studi Korelasional di Pondok Pesantren Daarul Qur’an Lampung Selatan - Sulistia Sahilatul Hayah; Muhammad Akmansyah; Riyan Terna Kuswanto (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
The ability to memorize the Qur’an constitutes an essential component of pesantren education, as it is not only associated with spiritual attainment but also closely related to cognitive discipline, concentration, and students’ academic development. This study aims to analyze the relationship between Qur’an memorization ability and students’ learning outcomes at Pondok Pesantren Daarul Qur’an, South Lampung. The study employed a quantitative approach with an ex post facto correlational design. The research was conducted in the odd semester of the 2025/2026 academic year at Pondok Pesantren Daarul Qur’an, South Lampung. The research sample was selected by including the entire available population. Data were collected using a Qur’an memorization ability questionnaire covering indicators of tahfidz, tajwid, and fluency, as well as a learning outcomes test encompassing cognitive levels from C1 to C6. The data were analyzed through validity testing, reliability testing, prerequisite testing, correlation analysis, hypothesis testing, and coefficient of determination analysis. The results indicate a positive correlation between Qur’an memorization ability and students’ learning outcomes. These findings suggest that strong memorization ability is associated with more optimal learning achievement through the reinforcement of discipline, focus, perseverance, and learning responsibility. This study implies the importance of integrating tahfiz programs with formal learning through effective time management, learning assistance, and continuous evaluation.